If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+8x=11x
We move all terms to the left:
8+8x-(11x)=0
We add all the numbers together, and all the variables
-3x+8=0
We move all terms containing x to the left, all other terms to the right
-3x=-8
x=-8/-3
x=2+2/3
| |y|=-18 | | 27x-265=5 | | n+6÷5=2 | | 3y^2-3y-429/4=0 | | 6(x+5)=41 | | 4x2+1=25 | | 3x+2x-45=15-10x+35 | | -(44(6)^2)/(25^2)+(6)+6=x | | (3x+5)(4x-1)=(6x-3)(2x+7) | | -(44(6)^2)/(25^2)+(6)+6=y | | x−0−=−4 | | 0.5x-2.5-x=1.5 | | 3x/4=7/8 | | 8=2h-2 | | 2/7c-1/14c=-3 | | -3k-8=5k | | (15x-13)+(8x+18)=90 | | 3+x/4=7/8 | | x−x−=−4 | | 35=7+r | | 15+x+x+x=51-x-x-x- | | 16=6+x/2 | | 10-j=14 | | (x+6)/(x-8)=0 | | 2x+8=5/2 | | 2x+8=5^2 | | 6x+9=15x+11 | | 6x^2-20x-25=0 | | 5-7w=25 | | 3m+7=10 | | -3(2x-8)=4x=4 | | 17=3+2j |